PERCEPTION OF PARENTS ASSISTANCE ABOUT OF HEALTH PROFESSIONALS IN A NEONATAL ICU OF A UNIVERSITY HOSPITAL IN WESTERN PARANÁ (Fiep Bulletin - online, 2014)
Meeting the needs and satisfaction of family members, especially parents of newborns admitted to neonatal intensive care units is an essential part of health care professionals. Accordingly, this study aimed to determine the perceptions of parents for assistance from health professionals in a neonatal intensive care unit of a teaching hospital in western Paraná. This is a descriptive, an exploratory, and a qualitative research. Sixteen individuals were interviewed from a semistructured writing interview. Responses were analyzed from the ordering and reading of the data, organized core categories. Most parents positively evaluated the care of professional in the intensive care unit, but there is a lack of information and communication between health professionals and families.is a lack of information and communication between health professionals and families.
Keywords: NICU; parents; health professional